UM ESTUDO SOBRE O CONCEITO DE MULTICULTURALISMO PRESENTE EM TRABALHOS ACADÊMICOS E SUA RELAÇÃO COM AS PRÁTICAS PEDAGÓGICAS - ZANIN, FLÁVIA ÂNGELA (2016)
Multiculturalism is the focus of this study because it is a topic that is present in the most recent discussions, as the current society has shown concerns inclusive perspectives for diversity. This paper aims to present an analysis of the Brazilian Graduate production in education, revealing that produced studies address on multiculturalism and how to include in their discussions, the issues surrounding multiculturalism relation to practices teaching. To meet the proposed objective and to develop arguments, the first stage of this dissertation outlines the theoretical look and the process of construction of the categories that guide the study. Next, proceed to the analysis of the data, discussing multiculturalism, and the categories that constitute it, as a research field. We conducted a search with criteria period (2003-2013), considering it was in that year approved the Law 10639/03. It was from this period that intensified multicultural issues, and recently that is expressed with greater definition. Being used to do so, the descriptors: multi / interculturalism, cultural diversity and education multi / intercultural, in the portal of CAPES. In the second stage, a selection of abstracts was conducted on the subject, which contemplated the main criteria. And finally, each production was selected analyzed seeking support in authors such as Bhaba (1998), Silva (2000), McLaren (2000), Hall (2003), and others. From the survey and taking as reference similar research, it was observed that the theme "Multiculturalism" is still little explored in education. It was found that the production of the Graduate Diploma in Education on the said topic, focuses more in the Southeast, followed by the South, the Northeast, the Midwest and North, respectively. It is believed the largest concentration in the South and Southeast is probably due to a larger number of higher education institutions in these regions. Being a relatively new subject, it was found that multiculturalism appeared timid way and should be further explored in academic research, in order to contribute, researchers and teachers in reflection processes, supporting the pedagogical practices to build a more just and democratic education.